Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao - Baroga-Barbecho, Jessica B.; Yap, Sheryl A.; Tan, Ming Kai; Robillard, Tony (Zootaxa, 2019)
The genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) is reviewed. New records and additional descriptions are provided for P. longipes Chopard, P. leytensis Robillard, and P. septentria Baroga, Yap & Robillard, and a new species is described from Mindanao: Paranisitra flavofacia n. sp. A taxonomic key and updated checklist of the genus Paranisitra in the world are also provided.